2018
DOI: 10.1155/2018/6852857
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiles of Propofol and Fospropofol: Clinical and Forensic Interpretative Aspects

Abstract: Propofol is an intravenous short-acting anesthetic widely used to induce and maintain general anesthesia and to provide procedural sedation. The potential for propofol dependency and abuse has been recognized, and several cases of accidental overdose and suicide have emerged, mostly among the health professionals. Different studies have demonstrated an unpredictable interindividual variability of propofol pharmacokinetics and pharmacodynamics with forensic and clinical adverse relevant outcomes (e.g., pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 179 publications
(195 reference statements)
1
50
0
2
Order By: Relevance
“…Search methodology was performed as described in previous publications on the metabolism and metabolomics of other drugs [5,[18][19][20][21][22][23][24][25][26][27]. Briefly, an English, Spanish, Portuguese and German extensive literature search was carried out in PubMed (U.S. National Library of Medicine) without a limiting period to identify relevant articles on pharmacoki-netics and pharmacodynamics of mescaline, related known metabolizing enzymes and metabolites, and effects of mescaline and peyote.…”
Section: Methodsologymentioning
confidence: 99%
“…Search methodology was performed as described in previous publications on the metabolism and metabolomics of other drugs [5,[18][19][20][21][22][23][24][25][26][27]. Briefly, an English, Spanish, Portuguese and German extensive literature search was carried out in PubMed (U.S. National Library of Medicine) without a limiting period to identify relevant articles on pharmacoki-netics and pharmacodynamics of mescaline, related known metabolizing enzymes and metabolites, and effects of mescaline and peyote.…”
Section: Methodsologymentioning
confidence: 99%
“…The incubation time used was 3 min to mimic the PR duration of action after bolus dose according to the drug PK/PD data. 36 After that, 170 μL of the supernatant was measured by HPLC–tandem mass spectrometry (HPLC–MS/MS) to determine the PR unbound fraction (fu prop ) according to a detailed protocol. Additionally, the bound PR fraction (fb prop ) was assessed as a difference of the fu 0 and fu prop values according to the equation where fu 0 is the unbound fraction (fu) of PR when the SA concentration is zero.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid clearance and awakening after a bolus of propofol occurs in humans as well as mice. 10 , 37 However, the behavioral, cognitive, neurophysiological and synaptic plasticity effects of propofol, ketamine, and brexanolone and other anesthetic agents have been reported to persist in rodents and humans substantially longer than would be anticipated by their pharmacokinetic and pharmacodynamic profiles alone. 2 , 4 , 11 , 17 , 26 , 27 , 33 , 34 , 38 , 39 , 40 , 41 For example, in their review, Browne and Lucki 41 observed that “the majority of studies indicate that the FST remains sensitive to the protracted effects of ketamine up to 1 week after a single injection.” Thus, the rapid clearance of propofol is unlikely to explain the lack of influence on an FST at 24 hours.…”
Section: Discussionmentioning
confidence: 99%